LEARNING LOSS DALAM PEMBELAJARAN GEOGRAFI: PELAKSANAAN SIMULASI BENCANA ALAM DI SMA NEGERI 60 JAKARTA - Nabilla, Lyzia; Hotimah, Oot; Sucahyanto (Jurnal Samudra Geografi, 2024)
The COVID-19 pandemic has necessitated changes in the realm of education. Ministry of Education and Culture Circular No. 4/2020 emphasizes that all activities, including learning, must be conducted from home to prevent the spread of the virus within schools. Online learning has encountered challenges, particularly in the implementation of practical activities. This research aims to identify learning loss among 11th-grade social science students at SMA Negeri 60 Jakarta during the COVID-19 pandemic through interviews and questionnaires